Pelaksanaan Didikan Subuh di Mda As-Syakirin Jorong Taluak Hilia IV Suku Kabupaten Agam - Riko, Riko; Aprison, Wedra (Indonesian Research Journal on Education, 2023)
This research was motivated by the problems found in MDA Asy-Syakirin, among others, the dawn education was often not on time, most of the dawn students did not perform the dawn prayer in congregation in the mosque, the lack of seriousness of the students in attending the dawn education. To find out how the implementation of Fajr Education activities at MDA Asy-Syakirin. This type of research is a research (Field Research) that is a qualitative descriptive field research, which tries to describe, describe and interpret a phenomenon that occurs in accordance with the data in the field. With key informants, namely ustad and ustazah and MDA students as supporting informants. To collect data the writer uses observation, interviews, and documentation as a data collection tool, and data analysis techniques using data reduction, data displayand data verification, and data validity by comparing the results of observations with interviews. Based on the results of the study, it can be concluded that the implementation of Subuh Education Activities at MDA AsySyakirin Jorong Taluak Iliah IV of the Nagari Taluak tribe has not run optimally, it can be seen that there arestill many students who do not pray at dawn in congregation in the mosque, there are still many students who arrive late while the event is already over. at the start, there are still students who are not PD when asked to read the Qur'an or perform, the lack of accountability of students with the tasks given to them, the method used by the tutor teacher has not gone well, but there are still some implementations which has been going well,namely All students read the assembly prayer in an orderly manner, The DDS and Mars DDS promises are read together, the teacher always comes on time, the teacher asks students questions about the material last week, the teacher explains the material clearly, the teacher always master the material he teaches to students, the teacher really enforces discipline to students, the teacher always evaluates at the end of the lesson, students read the kafaratu assembly prayer together, students take snacks in an orderly manner.